La Constitución de la República de Tunja de 1811: Acto independiente del ámbito español (2016)
Within the historical and constitutional scenario of Colombia, the Constitution of the Republic of Tunja in 1811, is a central and fundamental axel for the consolidation of the neogranadinians ideas which was created through the proclamation of the Congress of the United provinces, whose main focus is the role of the emancipation, independence and dedication of individual rights, economic development, political and social public powers and the and outlining of ideologies collected from the times of the French revolutions, English and American, in order to establish the day nine (09) of December of eighteen eleven (1811), in the province of Tunja, a federalist and capital central scheme of the revolution of independence against the regime of the Viceroyalty and the Spanish Crown, in that time of social order stabilization and a consolidation of Provincial States and a central point of the revolution.